Severe Combined Immunodeficiency (SCID): from molecular basisto clinical management - Sponzilli, I.; Notarangelo, L.D. (Acta Biomedica Atenei Parmensis, 2010)
Primary immune deficiency diseases (PID) comprise a genetically heterogeneous group of disorders that affect distinct components of the innate and adaptive immune system, such as neutrophils, macrophages, dendritic cells, complement proteins, natural killer cells, as well as T and B lymphocytes. Severe combined immunodeficiency (SCID) is a group of disorders characterized by increased susceptibility to severe infections and early death. The diagnosis of SCID is supported by the demonstration of low absolute lymphocyte count and T cell lymphopenia (variably associated with numerical defects of B and NK cells). In the last two decades, advances in the characterization of the molecular pathophysiology of SCID, have permitted the development of novel diagnostic assays based on analysis of the expression of the disease-associated proteins and mutation analysis. More recently, pilot newborn screening programs for the identification of infants with SCID have been initiated in the United States. Prompt and aggressive treatment of infections, antimicrobial prophylaxis (in particular against Pneumocystis jiroveci) and regular administration of immunoglobulins are essential to reduce the risk of early death. However, survival ultimately depends on reconstitution of immune function, that is usually achieved by means of hematopoietic cell transplantation (HCT). Gene therapy and enzyme replacement therapy have also been used successfully is selected forms of SCID. Here we review the molecular and cellular pathophysiology and the mainstay of treatment of SCID.